B-cell acute lymphoblastic leukemia with mature phenotype and MLL rearrangement: report of five new cases and review of the literature. Issue 10 (2nd October 2016) - Sajaroff, Elisa Olga; Mansini, Adrian; Rubio, Patricia; Alonso, Cristina Noemí; Gallego, Marta S.; Coccé, Mariela C.; Eandi-Eberle, Silvia; Bernasconi, Andrea Raquel; Ampatzidou, Maria; Paterakis, George; Papadhimitriou, Stefanos I.; Petrikkos, Loizos; et al.
Abstract: The association between mature-B phenotype and MLL abnormalities in acute lymphoblastic leukemia (ALL) is a very unusual finding; only 14 pediatric cases have been reported so far. We describe the clinical and biological characteristics and outcome of five pediatric cases of newly diagnosed B lineage ALL with MLL abnormalities and mature immunophenotype based on light chain restriction and surface Ig expression. Blasts showed variable expression of CD10/CD34/TdT. MLL abnormalities with no MYC involvement were detected in all patients by G-banding, FISH, and/or RT-PCR. Three patients were treated according to Interfant protocol, one to ALLIC-09, and one received B-NHL-BFM-2004. All patients achieved complete remission and three of them relapsed. Despite the small cohort size, it could be postulated that B lineage ALL with MLL abnormalities and mature phenotype is a distinct entity that differs both from the typical Pro B ALL observed in infants and mature B-ALL with high MYC expression.